History of the department of virology and molecular and biological methods of investigation of pediatric research and clinical center for infectious diseases - E. A. Murina; O. V. Goleva; Z. A. Osipova; A. L. Mukomolova (Журнал инфектологии, 2017)
The article deals with the history of formation of virology laboratory since 1963 after the resolution of the Academy of Medical Sciences of the USSR and the Ministry of Public Health on the expansion of virology investigation in the USSR.The results of the research work on studying various infections in children, developing new modified approaches to etiological express-diagnostics of the diseases, including those introduced into practice of the laboratory and regional medical centers are generalized. The laboratory got the name of the Department of Etiological Diagnostics Methods due to the basic direction of the research work. The primary goal of the department is to develop the methods and diagnostic algorithms for definite verification of infectious forms and the prognosis of the development of pathological process that allows determining the direction of further therapeutic approach to improve the disease outcome. In 2008 the Department of Etiological Diagnostics Methods began its «golden age» characterized by cardinal re-equipment and strengthening of the staff. There appeared the devices of expert class which completely replaced the manual testing process, the work connected with interpretation of serous meningitis outbreaks in Russia and the near abroad became more active.Now the department is a hi-technology scientific and practical center on studying viral and invasive forms of diseases with a priority direction of further innovations in laboratory diagnostics.